Efficacy of exogenous atrial natriuretic peptide in patients with heart failure with preserved ejection fraction: deficiency of atrial natriuretic peptide and replacement therapy. (10th October 2020) - Matsumoto, Shingo; Nakazawa, Gaku; Ohno, Yohei; Ishihara, Mai; Sakai, Katsuaki; Nakamura, Norihito; Murakami, Tsutomu; Natsumeda, Makoto; Kabuki, Takayuki; Shibata, Atsushi; Kida, Keisuke; Konishi, Masaaki; et al.
Abstract: Aims: Exogenous atrial natriuretic peptide (ANP) may be a logical treatment for heart failure (HF) patients with ANP deficiency. Lower ANP concentrations may result from HF with preserved ejection fraction (HFpEF), which also results in lower brain natriuretic peptide levels in HFpEF relative to HF with reduced ejection fraction (HFrEF), although clinical features regarding circulating ANP in HFpEF and HFrEF have not been fully investigated during acute HF. Here, we characterized the differential regulation of circulating ANP and the efficacy of exogenous ANP (carperitide) in patients with acute HF, especially HFpEF. Methods and results: Serum ANP levels before treatment and the diuretic effect of 0.0125 μg/kg/min of carperitide alone for the first 6 h were prospectively evaluated in 113 patients with acute HF who were divided into two groups: HFpEF vs. HFrEF. We mainly analysed the impact of baseline ANP levels and the presence of HFpEF on the diuretic effect of exogenous ANP. There was an inverse relationship between ANP levels and the diuretic effect of exogenous ANP ( r 2 = 0.19, P < 0.001). Patients with HFpEF had lower ANP levels ( P < 0.001) and a greater diuretic effect of exogenous ANP than patients HFrEF ( P < 0.001). HFpEF was an independent predictor of greater diuretic effect of exogenous ANP ( P = 0.003), as with a lower baseline ANP level ( P = 0.004). Conclusions: Patients with HFpEF might have an aspect of ANP deficiency and represent a promising therapeutic target for modulating circulating ANP.